KOMPARASI METODE PEMBELAJARAN MIND MAPPING DENGAN AUDIOVISUAL DALAM MATA PELAJARAN SKI TERHADAP HASIL BELAJAR SISWA DI MA DARUL ULUM BANDUNG JOMBANG - Hayati Hariyani F Ali Said; Ali Said (Kampus Akademik Publiser, 2024)
At the Darul Ulum Bandung MA there are most students who are less interested when learning SKI, with the presence of less interest and interest making less than the student's learning results. Based on the above background, the author would like to know how to compare the learning method of mind mapping with the visual audio learning method against student learning outcomes. The researchers themselves used comparative research experiments. The results of the research that has been carried out are 1). Student learning results using mind mapping in SKI subjects were ranked high with a presentation of 62.5% of 16 students and an average score of 65.62. 2). Student learning outcomes using visual audio method in the SKI subject ranked higher with a presentation of 56.25% of 16 pupils and a mean score of 80.62. 3). The calculation result using SPSS version 26 was obtained from the Mann Whitney test (0,004<0.05), this indicates that Ho was rejected and Ha accepted. It can be concluded that there is a comparison of learning outcomes of students using mind mapping and visual audio learning methods in students of class XII at Darul Ulum Bandung Jombang MA. Learning achievement of experimental group 1 students taught using mind mapping learning methods was lower compared to experimental groups 2 taught with visual audio learning method.